REPRESENTASI PEREMPUAN DAN ISU SOSIAL DALAM FILM AYAT-AYAT CINTA: ANALISIS PERSPEKTIF WARGANET - Istikomah, Anisa Maulidiya; Ardike, Happy Dwi; Aini, Nabila Nur; Afrizal, Mohamad (Asosiasi dosen IDEBAHASA KEPRI, 2025)
This study aims to analyze the themes in the comments of netizens on the Youtube platform about the movie Ayat Ayat Cinta. Adapted by Habiburrahman El Shirazy. The main focus is love, religion, culture, and feminism, related to the movie Ayat-Ayat Cinta. Using a qualitative method, this study adopted a discourse analysis approach to examine user-generated comments from YouTube videos, including trailers and reviews. Data collection was done by systematically selecting comments based on popularity, relevance, and interaction metrics. The analysis used thematic coding to identify recurring patterns in public discourse. The theoretical framework used includes mass communication theory to understand digital public engagement, feminist theory to explore gender portrayals, and literary theory to contextualize the societal narratives in the film. The results showed diverse opinions, ranging from praise of the Islamic values and moral ideals portrayed in the film to criticism of the passive portrayal of certain female characters. The research highlights YouTube as an interactive public space, reflecting broader cultural dynamics such as religious tolerance and gender roles. YouTube proved to be an interactive public space that reflects cultural dynamics such as tolerance and gender roles. This study recommends the exploration of other platforms, such as TikTok or Instagram, to expand the understanding of audience engagement with literary adaptations.